2013
DOI: 10.1016/j.scijus.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the discussion on the safety of air weapons

Abstract: Firearms legislation in the UK stems from the Firearms Act 1968 with its definition of a firearm as a lethal barrelled weapon of any description. The Act allows certain exceptions to be held without licence, most notably air weapons although these are limited by The Firearms (Dangerous Air Weapons) Rules 1969 and related regulations to below 12ft lb (16.3J) for air rifles and below 6ft lb (8.1J) for air pistols. Despite this there are occasional fatalities, typically 1 or 2 each year in the UK, from legally ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The jacket weave has not formed a cup, possibly due to the higher tensile strength of the thicker yarn, but there is evidence of tearing of the fibres from the yarn. In previous studies with animal and bird skin placed in contact with ballistic gel it has been observed that the combination is stronger than when skin was embedded in the gel [4] and in unpublished work on building materials it has been found that when layers of wood or plasterboard are in contact with each other, air rifle pellet penetration is reduced compared with cases where an air gap existed between the layers. It is thought that there is mutual support between the layers to absorb the energy of impact.…”
Section: Non-penetration Of the Clothingmentioning
confidence: 97%
See 2 more Smart Citations
“…The jacket weave has not formed a cup, possibly due to the higher tensile strength of the thicker yarn, but there is evidence of tearing of the fibres from the yarn. In previous studies with animal and bird skin placed in contact with ballistic gel it has been observed that the combination is stronger than when skin was embedded in the gel [4] and in unpublished work on building materials it has been found that when layers of wood or plasterboard are in contact with each other, air rifle pellet penetration is reduced compared with cases where an air gap existed between the layers. It is thought that there is mutual support between the layers to absorb the energy of impact.…”
Section: Non-penetration Of the Clothingmentioning
confidence: 97%
“…Other studies have investigated the missile energy necessary to penetrate skin [17] and it has been shown that an air-skin-gel boundary can behave differently from an air-gel-skin-gel boundary [4]. It is therefore of interest to consider cases where nonpenetration occurred.…”
Section: Non-penetration Of the Clothingmentioning
confidence: 99%
See 1 more Smart Citation
“…Their ballistic pattern of injury is poorly characterised compared with traditional firearms 3. One study4 investigating the ballistic profile of airgun pellets noted a difference between hunter (pointed) and bulldog (round ended) pellets. The bulldog pellet was associated with more tissue tearing and subsequently causing a higher morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors imply that "dieseling" increases muzzle velocity (12,22). Wightman et al (23) have demonstrated that a pellet shot with accompanying "dieseling" effect had a 33% higher speed than one shot without the use of excess oil in the barrel. We believe that putative increase in velocity and kinetic energy in cases of "dieseling" depends on the quantity of oil excess and the extent of combustion of that oil.…”
Section: Weapon and Ammunitionmentioning
confidence: 99%